Renal immature teratoma in infant: A rare case report - Yacobda Hamonangan Sigumonrong; Aze Andrea Putra (Urology Case Reports)
Renal teratoma is a rare malignant tumour originating from pluripotent cells. A five-month-old female presented with a painless abdominal mass initially suspected to be a Wilms tumor. A CT scan showed a large tumor in the left abdomen, leading to a left open nephrectomy. Histopathology confirmed an immature Grade III teratoma, showing ectodermal, mesodermal, and endodermal components with neuroepithelial structures. Post-operatively, the patient was stable with a good surgical wound. Diagnosis of renal teratoma relies on histology, as pre-operative imaging may mimic other tumors. Surgical removal is the primary treatment, with chemotherapy for recurrence if necessary.